A rare Fusarium equiseti infection in a 53-year-old male with burn injury: A case report - Tang Hai; Nguyen Minh; Do Anh; Tran Dung; Ngo Chau; Le Tran-Anh (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: Burn injuries are prone to infection caused by bacteria, fungi, or other pathogens. Fungal wound infection usually has non-specific clinical symptoms.Nevertheless, in some cases, the fungal burden is so substantial that can easily be seen by the naked eyes, but this phenomenon has rarely been reported with Fusarium. Case report: A 53-year-old patient with severe burn injury was admitted to the intensive care unit of the National Hospital of Burn, Ha Noi, Vietnam. His wound was dressed with a traditional herbal product before the hospital admission. On the 5th day after the admission, some white patches suspected of fungal colonies appeared on burn lesions where the herbal medicine was placed. Histological examination (Periodic acidSchiff) and culture of biopsy samples taken from those lesions revealed fungus that was identified as Fusarium equiseti after analysis of the internal transcribed spacer and D1/D2 region of the large subunit of the 28S rDNA. The isolated strain showed susceptibility to voriconazole but resistance to fluconazole, itraconazole, caspofungin,and amphotericin B in vitro. The patient received aggressive treatment, including IV voriconazole (400 mg daily from day five); however, he could not recover. Conclusion: Fusarium should be suspected in burn patients with white patches on lesions. Antifungal susceptibility testing is important since multidrug resistance is common among Fusarium strains.